High-airtightness concrete and preparation method thereof
By using modified fibers and aqueous polyurethane emulsions in concrete to form a three-dimensional spiral structure, the problem of poor airtightness of existing concrete is solved, and the effect of efficient gas leakage is achieved, which significantly improves the airtightness and safety of concrete.
Patent Information
- Application Number
- CN202510143404.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-10
- Publication Date
- 2025-04-15
AI Technical Summary
The existing concrete has high porosity, poor airtightness and permeability resistance, which leads to the inability to effectively prevent gas and other harmful gas leakage in road and railway tunnel projects, increasing the life safety risks of construction workers and users.
A high-air-tight concrete is used, and its composition includes silicate cement, coarse aggregate, fine aggregate, air-tight modifier, water reducing agent, air-tight agent, internal curing agent and appropriate amount of water. The air-tight modifier is composed of plasma-modified polyethylene fiber, carbon fiber and water-based polyurethane emulsion. By modifying the fiber surface and forming a three-dimensional spiral structure, the porosity of the concrete is significantly reduced.
It significantly improves the airtightness of concrete, can effectively prevent leakage of gas and other harmful gases, reduces the risk factor in tunnel projects, and ensures the personal safety of construction workers.
Smart Images

Figure BDA0005265608620000151 
Figure BDA0005265608620000162
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of building materials, and specifically relates to a high-airtightness concrete and a preparation method thereof. Background Art
[0002] In the prior art, concrete is an artificial stone material that is prepared from cementitious materials, aggregates and water in a certain proportion, stirred and vibrated into shape, and cured under certain conditions. It can be classified into structural concrete, road concrete, hydraulic concrete and special concrete according to its use. It is widely used in construction projects, road projects, bridge projects, water conservancy projects, etc.
[0003] In the prior art, the water-cement ratio of traditional concrete is usually 0.40-0.65. Although it still has excellent structural properties, its porosity is relatively high, and its air tightness and anti-permeability properties are relatively poor. In actual application, harmful substances such as gas and water vapor outside the concrete will enter the interior of the concrete, causing steel corrosion inside the concrete, expansion of internal cracks and degradation of concrete quality, thereby affecting the overall performance and service life of the structure. Furthermore, in some special usage scenarios of concrete, such as in highway and railway tunnel projects, the existing concrete has a high porosity and poor air tightness. When the tunnel passes through a coal seam rock containing gas, the existing concrete cannot effectively prevent the leakage of gas and other harmful gases, which increases the risk factor in tunnel projects and endangers the lives of construction workers and users.
[0004] Therefore, in order to meet the construction needs of highway and railway tunnel projects, there is an urgent need for a highly airtight concrete to effectively prevent the leakage of gas and other harmful gases in highway and railway tunnel projects. Summary of the invention
[0005] The present application aims to solve the technical problems in the prior art that the conventional concrete has a high water-binder ratio, a high porosity, and poor air tightness and anti-permeability performance. In the actual application process, harmful substances such as gas and water vapor outside the concrete will enter the concrete and even pass through the concrete layer. In highway and railway tunnel projects, when the tunnel passes through coal seam rock containing gas, the existing concrete cannot effectively prevent the leakage of gas and other harmful gases, which increases the risk factor in the tunnel project, endangers the life safety of construction workers and users, and cannot meet the construction needs of highway and railway tunnel projects. A high air tightness concrete is proposed;
[0006] In order to solve the technical problem proposed by the present application, the present application also proposes a method for preparing high airtight concrete;
[0007] In order to solve the technical problem proposed in this application, this application also proposes an application of high airtightness concrete.
[0008] The present application adopts the following scheme: a high airtightness concrete, which is composed of the following components by weight: 37-49 parts of silicate cement, 95-113 parts of coarse aggregate, 77-85 parts of fine aggregate, 26-36 parts of airtightness modifier, 2-5 parts of water reducing agent, 1-3 parts of air entraining agent, 1-3 parts of internal curing agent and appropriate amount of water;
[0009] Wherein, the air tightness modifier is composed of the following components by weight: 6-7 parts of plasma-modified polyethylene fiber, 5-8 parts of carbon fiber and 15-20 parts of waterborne polyurethane emulsion;
[0010] The water-cement ratio of the high airtightness concrete is 0.21-0.27.
[0011] In some feasible embodiments, the air entraining agent is selected from any one of rosin-based air entraining agents, alkylbenzene sulfonate-based air entraining agents, saponin-based air entraining agents, or a combination of more than one of the following:
[0012] More preferably, the air entraining agent is a saponin air entraining agent.
[0013] In some feasible embodiments, the water reducer is selected from any one of lignin sulfonate water reducer, naphthalene-based high-efficiency water reducer, melamine-based high-efficiency water reducer, polycarboxylic acid-based high-performance water reducer, and aminosulfonate-based high-efficiency water reducer, or a combination of more than one of them.
[0014] More preferably, the water reducing agent is a polycarboxylic acid-based high-performance water reducing agent.
[0015] In some feasible embodiments, the method for preparing the plasma-modified polyethylene fiber comprises the following steps:
[0016] Step 101. Put the polyethylene fiber and excess acetone into a soaking tank, soak the polyethylene fiber in acetone for 20 minutes to 30 minutes, and after the soaking is completed, wash with deionized water and dry in sequence to obtain primary polyethylene fiber;
[0017] Step 102. The primary polyethylene fiber prepared in step 101 and excess acid solution A are put into a pickling tank, and the primary polyethylene fiber is immersed in the acid solution for 30s-50s. After the pickling is completed, the fiber is neutralized with alkaline solution, washed with deionized water, and dried to obtain a secondary polyethylene fiber.
[0018] Step 103: Transfer the secondary polyethylene fiber prepared in step 102 to the reaction chamber of a plasma cleaning machine, extract the gas impurities in the reaction chamber, and 2Under the conditions of atmosphere, reaction chamber pressure of 150Pa-220Pa, output DC voltage of 720V, and output power of 30W, after reacting for 4min-6min, plasma-modified polyethylene fiber was obtained.
[0019] In some feasible embodiments, the model of the plasma cleaning machine in step 103 is PDC-36G.
[0020] During the actual implementation process, the polyethylene fiber is treated with acid solution A to remove the weak interface layer on the surface, and then transferred to a plasma cleaning machine. The surface of the polyethylene fiber is bombarded with nitrogen ions to improve the roughness of the polyethylene fiber surface, form micropores or grooves on the polyethylene fiber surface, increase the specific surface area of the polyethylene fiber, and introduce a large number of polar groups such as -COOH and -OH into the micropores or grooves on the surface of the polyethylene fiber, which significantly improves the interface connection performance of the polyethylene fiber.
[0021] In some feasible embodiments, the carbon fiber is subjected to surface modification treatment, and the surface modification treatment comprises the following steps:
[0022] Step 201. Put the carbon fiber and excess acetone into a soaking tank, soak the carbon fiber in acetone at 120° C. and 2.2 MPa for 11 min to 16 min. After the soaking is completed, wash with deionized water and dry in turn to obtain primary carbon fiber;
[0023] Step 202. The primary carbon fiber, potassium dichromate powder and acid solution B prepared in step 101 are put into a pickling tank, and the primary carbon fiber is soaked in the acid solution for 11s-17s. After the pickling is completed, the primary carbon fiber is neutralized with alkaline solution, washed with deionized water and dried to obtain secondary carbon fiber;
[0024] In some feasible embodiments, the mass ratio of primary carbon fiber, potassium dichromate powder and acid solution B is (6.5-7.5):(11.3-12.5):117;
[0025] Step 203. Put the secondary carbon fiber and tetrabutyl titanate prepared in step 202 into a reactor, and react for 12 min-18 min in a water bath at 50° C., a reaction pressure of 1.3 MPa, and a stirring frequency of 1200 rpm-1500 rpm to obtain a finished carbon fiber product.
[0026] In some feasible embodiments, the mass ratio of the secondary carbon fiber to tetrabutyl titanate is 1.3:(12.2-14.5);
[0027] In some feasible embodiments, in step 101, the diameter of the polyethylene fiber is 14 μm-18 μm, the length of the polyethylene fiber is 7 mm-14 mm, and the elastic modulus of the polyethylene fiber is 88 GPa-91 GPa;
[0028] In some feasible embodiments, the polyethylene fiber is of type Dyneema SK75 / Spectra 900.
[0029] During the actual implementation process, after the surface isolation layer of the carbon fiber is removed by acid liquid B, a large number of micropores or surface grooves are formed on the surface of the carbon fiber through a short immersion in acid liquid B, which significantly increases the specific surface area of the carbon fiber. The acid liquid B contains HF, which can effectively introduce CF on the surface of the carbon fiber. After immersion in tetrabutyl titanate, CF can capture the polar groups in tetrabutyl titanate and introduce a large number of connection sites on the surface of the carbon fiber, thereby significantly improving the interface connection performance of the carbon fiber.
[0030] In step 201 , the diameter of the carbon fiber is 10 μm-15 μm, the length of the carbon fiber is 5 mm-10 mm, and the elastic modulus of the carbon fiber is 220 GPa-250 GPa.
[0031] In some feasible embodiments, in step 102, the acid solution A is a sulfuric acid solution with a mass fraction of 43%-57%;
[0032] In step 202, the acid solution B is prepared by compounding a hydrochloric acid solution with a mass fraction of 31%-36% and a hydrofluoric acid solution with a mass fraction of 41%-55% in a mass ratio of 5:1.
[0033] In some feasible embodiments, the preparation method of the airtightness modifier includes the following steps: plasma-modified polyethylene fiber, carbon fiber and aqueous polyurethane emulsion are sequentially put into a reactor according to a preset proportion, and the reaction is carried out for 20min-33min under the conditions of a reaction temperature of 48°C-55°C, a reaction pressure of -0.01MPa and a stirring frequency of 1100rpm-1300rpm to obtain the airtightness modifier.
[0034] In the actual implementation process, by designing the diameters of carbon fiber and polyethylene fiber and cooperating with water-based polyurethane emulsion, the carbon fiber with smaller diameter will entangle the polyethylene fiber with larger diameter to form a three-dimensional spiral structure. During the concrete preparation process, the temperature of the concrete system rises, the water in the water-based polyurethane emulsion evaporates, and the three-dimensional spiral structure fills the gaps between the components of the concrete. As the water in the emulsion further evaporates, the functional components in the emulsion are further enriched in the gaps between the components of the concrete, and capture the fine aggregate (microsilica powder, etc.) in the concrete system, further improving the spatial folding degree of the three-dimensional spiral structure, thereby significantly reducing the porosity of the concrete system. Through the three-dimensional spiral structure, the diffusion range of gas molecules is increased, which can effectively limit the diffusion movement of gas molecules in concrete, thereby significantly improving the airtightness of the concrete.
[0035] In some feasible embodiments, the coarse aggregate is selected from any one of basalt, pebble, limestone, granite, gabbro, gneiss, marble, or a mixture of more than one of them.
[0036] Preferably, the coarse aggregate is a combination of basalt, pebbles and marble;
[0037] More preferably, the coarse aggregate is obtained by compounding basalt, pebbles and marble in a mass ratio of 5:2:2.
[0038] In some feasible embodiments, the fine aggregate is selected from any one of zeolite powder, slag, river sand, waste glass powder, volcanic ash, rice husk ash, lime powder, glutinous rice flour, coal powder, and microsilica powder, or a mixture of more than one of them.
[0039] Preferably, the fine aggregate is a mixture of zeolite powder, river sand, waste glass powder, glutinous rice flour and microsilica powder.
[0040] More preferably, the fine aggregate is obtained by compounding zeolite powder, river sand, waste glass powder, glutinous rice flour and microsilica powder in a mass ratio of 2:5:1:1.5:7.
[0041] In some feasible embodiments, the particle size of the coarse aggregate is 40 mm-60 mm;
[0042] The particle size of the fine aggregate is 5 μm-12 μm, and the specific surface area of the fine aggregate is 145000 cm 2 / g-188500cm 2 / g.
[0043] In order to solve the technical problem raised by the present application, the present application also provides a method for preparing high airtight concrete, comprising the following steps:
[0044] Step 301. Ingredients: weigh each component according to the preset target ratio for later use;
[0045] Step 302. Primary mixing: Put silicate cement and coarse aggregate into a concrete mixer, and stir for 15 minutes at room temperature and a stirring frequency of 1500 rpm to obtain a primary mixture;
[0046] Step 303. Mixing again: Put the primary mixture, fine aggregate, air tightness modifier, water reducer, air entraining agent, internal curing agent and appropriate amount of water into a concrete mixer in sequence, and stir for 20 minutes at a stirring temperature of 60° C., a stirring pressure of -0.05 MPa and a stirring frequency of 1200 rpm to obtain a high air tightness concrete product.
[0047] In order to solve the technical problem proposed in this application, this application also proposes an application of high airtightness concrete, which is applied to tunnel construction projects and is used to pass through rock formations containing gas in highway and railway projects.
[0048] Compared with the prior art, this application has the following beneficial effects:
[0049] The present application provides a high-airtightness concrete, a preparation method thereof and an application thereof, wherein the high-airtightness concrete is composed of silicate cement, coarse aggregate, fine aggregate, an airtightness modifier, a water reducer, an air entraining agent, an internal curing agent and an appropriate amount of water, wherein the airtightness modifier is composed of plasma-modified polyethylene fiber, carbon fiber and water-based polyurethane emulsion, and the polyethylene fiber and the carbon fiber are modified, the connection sites on the surface of the polyethylene fiber and the carbon fiber are enriched, and a three-dimensional spiral network structure is formed in combination with the water-based polyurethane emulsion, and the airtightness modifier is introduced into the concrete system, and the three-dimensional spiral network structure can be filled between the components, and combined with silicate cement and aggregate, the gaps between the components are filled, and the three-dimensional network structure is filled in the gaps between the components, so as to effectively reduce the porosity of the concrete and significantly improve the airtightness of the concrete. When the tunnel passes through a coal seam rock mass containing gas, the leakage of harmful gases such as gas can be effectively prevented, the risk factor in the tunnel project can be reduced, and the personal safety of the construction personnel can be ensured. The concrete has the advantages of simple operation, broad application prospects and easy promotion and implementation. DETAILED DESCRIPTION
[0050] Combined with the contents shown in Examples 1-3 and Comparative Examples 1-6, the technical solution provided by the present application is further explained.
[0051] The average diameter of the polyethylene fibers is 15.7 μm, the average length of the polyethylene fibers is 10.9 mm, and the average elastic modulus of the polyethylene fibers is 88.7 GPa.
[0052] The average diameter of the carbon fibers is 11.2 μm, the average length of the carbon fibers is 7.9 mm, and the average elastic modulus of the carbon fibers is 236.1 GPa.
[0053] Acid solution A is a sulfuric acid solution with a mass fraction of 45.9%.
[0054] Acid solution B is prepared by mixing a hydrochloric acid solution with a mass fraction of 33.1% and a hydrofluoric acid solution with a mass fraction of 47.8% in a mass ratio of 5:1.
[0055] The coarse aggregate is obtained by mixing basalt, pebble and marble in a mass ratio of 5:2:2.
[0056] The fine aggregate is obtained by compounding zeolite powder, river sand, waste glass powder, glutinous rice flour and microsilica powder in a mass ratio of 2:5:1:1.5:7.
[0057] The average particle size of coarse aggregate is 55.8 mm.
[0058] The average particle size of the fine aggregate is 11.7 μm, and the average specific surface area of the fine aggregate is 171510 cm 2 / g.
[0059] The amount of water is adjusted according to the target water-binder ratio of high airtight concrete.
[0060] Example 1
[0061] (1) The preparation of plasma-modified polyethylene fibers comprises the following steps:
[0062] Step 101. Put the polyethylene fiber and excess acetone into a soaking tank, soak the polyethylene fiber in acetone for 22 minutes, and after the soaking is completed, wash with deionized water and dry in sequence to obtain primary polyethylene fiber;
[0063] Step 102. The primary polyethylene fiber prepared in step 101 and excess acid solution A are put into a pickling tank, and the primary polyethylene fiber is immersed in the acid solution for 30 seconds. After the pickling is completed, the fiber is neutralized with alkaline solution, washed with deionized water, and dried to obtain a secondary polyethylene fiber.
[0064] Step 103: Transfer the secondary polyethylene fiber prepared in step 102 to the reaction chamber of a plasma cleaning machine, extract the gas impurities in the reaction chamber, and 2 Under the conditions of atmosphere, reaction chamber pressure of 153Pa, output DC voltage of 720V and output power of 30W, after reacting for 4 minutes, plasma-modified polyethylene fiber was obtained.
[0065] (2) The carbon fiber surface modification treatment includes the following steps:
[0066] Step 201. Put the carbon fiber and excess acetone into a soaking tank, soak the carbon fiber in acetone at 120° C. and 2.2 MPa for 12 minutes, and wash with deionized water and dry in turn to obtain primary carbon fiber;
[0067] Step 202. The primary carbon fiber, potassium dichromate powder and acid solution prepared in step 101 are put into a pickling tank in a mass ratio of 6.5:11.3:117, and the primary carbon fiber is soaked in the acid solution for 12 seconds. After the pickling is completed, the primary carbon fiber is neutralized with alkaline solution, washed with deionized water and dried to obtain secondary carbon fiber;
[0068] Step 203. The secondary carbon fiber prepared in step 202 and tetrabutyl titanate are added into a reactor at a mass ratio of 1.3:12.2, and react for 12 minutes in a water bath at 50°C, a reaction pressure of 1.3 MPa, and a stirring frequency of 1255 rpm to obtain a finished carbon fiber product.
[0069] (3) The preparation method of the airtightness modifier comprises the following steps:
[0070] Plasma-modified polyethylene fiber, carbon fiber and aqueous polyurethane emulsion are sequentially put into the reactor according to a preset ratio, and reacted for 20 minutes under the conditions of reaction temperature of 48°C, reaction pressure of -0.01MPa and stirring frequency of 1150rpm to obtain an airtightness modifier.
[0071] (4) The preparation of high airtight concrete comprises the following steps:
[0072] Step 301. Ingredients: weigh each component according to the component table shown in Table 1;
[0073] Step 302. Primary mixing: according to the component table shown in Table 1, put silicate cement and coarse aggregate into a concrete mixer, and stir for 15 minutes at room temperature and a stirring frequency of 1500 rpm to obtain a primary mixture;
[0074] Step 303. Mixing again: according to the component table shown in Table 1, the primary mixture, fine aggregate, air tightness modifier, water reducer, air entraining agent, internal curing agent and appropriate amount of water are sequentially put into a concrete mixer, and stirred for 20 minutes under the conditions of a stirring temperature of 60° C., a stirring pressure of -0.05 MPa and a stirring frequency of 1200 rpm to obtain a high air tightness concrete product.
[0075] Among them, the water-cement ratio of the finished high airtight concrete product is 0.22.
[0076] Example 2
[0077] (1) The preparation of plasma-modified polyethylene fibers comprises the following steps:
[0078] Step 101. Put the polyethylene fiber and excess acetone into a soaking tank, soak the polyethylene fiber in acetone for 25 minutes, and after the soaking is completed, wash with deionized water and dry in sequence to obtain primary polyethylene fiber;
[0079] Step 102. The primary polyethylene fiber prepared in step 101 and excess acid solution A are put into a pickling tank, and the primary polyethylene fiber is immersed in the acid solution for 40 seconds. After the pickling is completed, the fiber is neutralized with alkaline solution, washed with deionized water, and dried to obtain a secondary polyethylene fiber.
[0080] Step 103: Transfer the secondary polyethylene fiber prepared in step 102 to the reaction chamber of a plasma cleaning machine, extract the gas impurities in the reaction chamber, and 2 Under the conditions of atmosphere, reaction chamber pressure of 180Pa, output DC voltage of 720V and output power of 30W, after reacting for 5 minutes, plasma-modified polyethylene fiber was obtained.
[0081] (2) The carbon fiber surface modification treatment includes the following steps:
[0082] Step 201. Put the carbon fiber and excess acetone into a soaking tank, soak the carbon fiber in acetone at 120° C. and 2.2 MPa for 13 min. After the soaking is completed, wash with deionized water and dry in turn to obtain primary carbon fiber;
[0083] Step 202. The primary carbon fiber, potassium dichromate powder and acid solution prepared in step 101 are put into a pickling tank in a mass ratio of 7:11.7:117, and the primary carbon fiber is soaked in the acid solution for 14 seconds. After the pickling is completed, the primary carbon fiber is neutralized with alkali solution, washed with deionized water and dried to obtain secondary carbon fiber;
[0084] Step 203. The secondary carbon fiber prepared in step 202 and tetrabutyl titanate are added into a reactor at a mass ratio of 1.3:13.5, and reacted for 15 minutes in a water bath at 50°C, a reaction pressure of 1.3 MPa, and a stirring frequency of 1355 rpm to obtain a finished carbon fiber product.
[0085] (3) The preparation method of the airtightness modifier comprises the following steps:
[0086] Plasma-modified polyethylene fiber, carbon fiber and aqueous polyurethane emulsion are sequentially put into the reactor according to a preset ratio, and reacted for 26 minutes under the conditions of reaction temperature of 51°C, reaction pressure of -0.01MPa and stirring frequency of 1200rpm to obtain an airtightness modifier.
[0087] (4) The preparation of high airtight concrete comprises the following steps:
[0088] Step 301. Ingredients: weigh each component according to the component table shown in Table 1;
[0089] Step 302. Primary mixing: according to the component table shown in Table 1, put silicate cement and coarse aggregate into a concrete mixer, and stir for 15 minutes at room temperature and a stirring frequency of 1500 rpm to obtain a primary mixture;
[0090] Step 303. Mixing again: according to the component table shown in Table 1, the primary mixture, fine aggregate, air tightness modifier, water reducer, air entraining agent, internal curing agent and appropriate amount of water are sequentially put into a concrete mixer, and stirred for 20 minutes under the conditions of a stirring temperature of 60° C., a stirring pressure of -0.05 MPa and a stirring frequency of 1200 rpm to obtain a high air tightness concrete product.
[0091] Among them, the water-cement ratio of the finished high airtight concrete product is 0.25.
[0092] Example 3
[0093] (1) The preparation of plasma-modified polyethylene fibers comprises the following steps:
[0094] Step 101. Put the polyethylene fiber and excess acetone into a soaking tank, soak the polyethylene fiber in acetone for 30 minutes, and after the soaking is completed, wash with deionized water and dry in sequence to obtain primary polyethylene fiber;
[0095] Step 102. The primary polyethylene fiber prepared in step 101 and excess acid solution A are put into a pickling tank, and the primary polyethylene fiber is immersed in the acid solution for 50 seconds. After the pickling is completed, the fiber is neutralized with alkaline solution, washed with deionized water, and dried to obtain a secondary polyethylene fiber.
[0096] Step 103: Transfer the secondary polyethylene fiber prepared in step 102 to the reaction chamber of a plasma cleaning machine, extract the gas impurities in the reaction chamber, and 2 Under the conditions of atmosphere, reaction chamber pressure of 220Pa, output DC voltage of 720V and output power of 30W, after reacting for 6 minutes, plasma-modified polyethylene fiber was obtained.
[0097] (2) The carbon fiber surface modification treatment includes the following steps:
[0098] Step 201. Put the carbon fiber and excess acetone into a soaking tank, soak the carbon fiber in acetone at 120° C. and 2.2 MPa for 16 min. After the soaking is completed, wash with deionized water and dry in turn to obtain primary carbon fiber;
[0099] Step 202. The primary carbon fiber, potassium dichromate powder and acid solution prepared in step 101 are put into a pickling tank in a mass ratio of 7.5:12.5:117, and the primary carbon fiber is soaked in the acid solution for 17 seconds. After the pickling is completed, the primary carbon fiber is neutralized with alkaline solution, washed with deionized water and dried to obtain secondary carbon fiber;
[0100] Step 203. The secondary carbon fiber prepared in step 202 and tetrabutyl titanate are added into a reactor at a mass ratio of 1.3:14.5, and reacted for 18 minutes in a water bath at 50°C, a reaction pressure of 1.3 MPa, and a stirring frequency of 1500 rpm to obtain a finished carbon fiber product.
[0101] (3) The preparation method of the airtightness modifier comprises the following steps:
[0102] Plasma-modified polyethylene fiber, carbon fiber and aqueous polyurethane emulsion are sequentially put into the reactor according to a preset ratio, and reacted for 33 minutes under the conditions of reaction temperature of 55°C, reaction pressure of -0.01MPa and stirring frequency of 1300rpm to obtain an airtightness modifier.
[0103] (4) The preparation of high airtight concrete comprises the following steps:
[0104] Step 301. Ingredients: weigh each component according to the component table shown in Table 1;
[0105] Step 302. Primary mixing: according to the component table shown in Table 1, put silicate cement and coarse aggregate into a concrete mixer, and stir for 15 minutes at room temperature and a stirring frequency of 1500 rpm to obtain a primary mixture;
[0106] Step 303. Mixing again: according to the component table shown in Table 1, the primary mixture, fine aggregate, air tightness modifier, water reducer, air entraining agent, internal curing agent and appropriate amount of water are sequentially put into a concrete mixer, and stirred for 20 minutes under the conditions of a stirring temperature of 60° C., a stirring pressure of -0.05 MPa and a stirring frequency of 1200 rpm to obtain a high air tightness concrete product.
[0107] Among them, the water-cement ratio of the finished high airtight concrete product is 0.27.
[0108] Comparative Example 1
[0109] The air tightness modifier in Example 3 was removed and supplemented with silicate cement and water to control the water-cement ratio of the finished concrete product to 0.27.
[0110] Comparative Example 2
[0111] The plasma modified fibers in the air tightness modifier in Example 3 were removed and supplemented with silicate cement and water to control the water-cement ratio of the finished concrete product to 0.27.
[0112] Comparative Example 3
[0113] The carbon fiber in the airtightness modifier in Example 3 was removed and supplemented with silicate cement and water to control the water-cement ratio of the finished concrete product to 0.27.
[0114] Comparative Example 4
[0115] The water-based polyurethane emulsion in the airtightness modifier in Example 3 was removed and supplemented with silicate cement and water to control the water-cement ratio of the finished concrete product to 0.27.
[0116] Comparative Example 5
[0117] The plasma modification step of the polyethylene fiber in Example 3 was removed, and the process flow of other components remained unchanged.
[0118] Comparative Example 6
[0119] The carbon fiber surface modification step in Example 3 was removed, and the process flow of other components remained unchanged.
[0120] Table 1 Components of Examples 1-3 and Comparative Examples 1-4
[0121]
[0122]
[0123] Table 1
[0124]
[0125] The finished concrete products prepared in Examples 1-3 and Comparative Examples 1-6 were subjected to the following tests:
[0126] Test 1: Referring to GB / T 50080-2016, the slump of the finished concrete products prepared in Examples 1-3 and Comparative Examples 1-6 was tested;
[0127] Test 2: Referring to GB / T 21650.1-2008, the porosity of the finished concrete products prepared in Examples 1-3 and Comparative Examples 1-6 was tested;
[0128] Test 3: Referring to GB / T 50081-2019, the finished concrete products prepared in Examples 1-3 and Comparative Examples 1-6 were prepared into experimental pieces, and the mechanical properties (compressive strength, splitting tensile strength and crack resistance) of the concrete test pieces were tested;
[0129] Test 4: Referring to GB / T 50081-2019, the finished concrete products prepared in Examples 1-3 and Comparative Examples 1-6 were prepared into test pieces, and the connection strength of each component in the concrete test pieces was tested;
[0130] Test 5: Referring to GB / T50082-2009, the finished concrete products prepared in Examples 1-3 and Comparative Examples 1-6 were prepared into test pieces, and the chloride ion penetration resistance of the concrete test pieces was tested to test the air tightness of the concrete test pieces. The test results are shown in Table 2 below.
[0131] Table 2 Test results of Examples 1-3 and Comparative Examples 1-6
[0132] Test items Example 1 Example 2 Example 3 Slump(mm) 185 188 187 Porosity (%) 5.9 6.2 6.1 Compressive strength(MPa) 163.7 159.2 160.8 Splitting strength(MPa) 12.3 11.7 11.9 Connection strength (MPa) 8.7 9.4 9.2 <![CDATA[DRCM(10 -12 m 2 / s)]]> 0.67 0.69 0.66 Cracking grade Level I Level I Level I
[0133] Table 2
[0134] Test items Comparative Example 1 Comparative Example 2 Comparative Example 3 Slump(mm) 201 195 197 Porosity (%) 13.6 10.2 11.3 Compressive strength(MPa) 105.1 128.5 137.3 Splitting strength(MPa) 7.6 8.9 9.3 Connection strength (MPa) 4.5 6.1 7.7 <![CDATA[DRCM(10 -12 m 2 / s)]]> 9.8 5.1 4.6 Cracking grade Level III Level I Level I
[0135] Table 2
[0136] Test items Comparative Example 4 Comparative Example 5 Comparative Example 6 Slump(mm) 210 193 187 Porosity (%) 8.3 7.9 7.5 Compressive strength(MPa) 139.8 142.6 138.7 Splitting strength(MPa) 9.4 10.1 9.9 Connection strength (MPa) 7.5 7.1 7.3 <![CDATA[DRCM(10 -12 m 2 / s)]]> 2.9 2.6 2.1 Cracking grade Level II Level I Level I
[0137] As can be seen from the above, in Examples 1-3, an airtightness modifier is introduced into the concrete gel system, wherein the airtightness modifier is composed of plasma-modified polyethylene fiber, surface-modified carbon fiber and aqueous polyurethane emulsion. The polyethylene fiber is treated with acid solution A to remove the weak interface layer on the surface, and then transferred to a plasma cleaning machine. 2 In the atmosphere, the surface of the polyethylene fiber is bombarded with nitrogen ions, which improves the roughness of the polyethylene fiber surface, forms micropores or grooves on the polyethylene fiber surface, increases the specific surface area of the polyethylene fiber, and introduces a large number of polar groups such as -COOH and -OH into the micropores or grooves on the surface of the polyethylene fiber, which significantly improves the interface connection performance of the polyethylene fiber;
[0138] After the carbon fiber is treated with acid liquid B to remove the surface isolation layer, a large number of micropores or surface grooves are formed on the surface of the carbon fiber through a short period of immersion in acid liquid B, which significantly increases the specific surface area of the carbon fiber. Acid liquid B contains HF, which can effectively introduce CF on the surface of the carbon fiber. After immersion in tetrabutyl titanate, CF can capture the polar groups in tetrabutyl titanate and introduce a large number of connection sites on the surface of the carbon fiber, thereby significantly improving the interface connection performance of the carbon fiber.
[0139] By designing the diameters of carbon fiber and polyethylene fiber and combining with water-based polyurethane emulsion, the carbon fiber with smaller diameter will entangle the polyethylene fiber with larger diameter to form a three-dimensional spiral structure. During the concrete preparation process, the temperature of the concrete system rises, the water in the water-based polyurethane emulsion evaporates, and the three-dimensional spiral structure fills the gaps between the components of the concrete. As the water in the emulsion further evaporates, the functional components in the emulsion are further enriched in the gaps between the components of the concrete and capture the fine aggregate (microsilica powder, etc.) in the concrete system, further improving the spatial folding degree of the three-dimensional spiral structure, thereby significantly reducing the porosity of the concrete system. Through the three-dimensional spiral structure, the diffusion range of gas molecules is increased, which can effectively limit the diffusion movement of gas molecules in concrete, thereby significantly improving the airtightness of the concrete.
[0140] From the test results in Table 2, it can be seen that in Comparative Example 1, the airtightness modifier was removed, the three-dimensional spiral structure was not introduced into the concrete system, the gap filling effect between the components was poor, the concrete system had high porosity and poor airtightness, and could not meet the construction requirements of highway and railway tunnel projects;
[0141] In Comparative Example 2, the plasma modified fiber in the air tightness modifier was removed, and the single carbon fiber could not form a three-dimensional spiral structure during the concrete preparation process, the filling effect between the components was poor, the concrete system had high porosity and poor air tightness, and could not meet the construction requirements of highway and railway tunnel projects;
[0142] In Comparative Example 3, the carbon fiber in the air tightness modifier is removed, and the single polyethylene fiber is difficult to form a three-dimensional spiral structure during the concrete preparation process, the filling effect between the components is poor, the concrete system has high porosity and poor air tightness, and cannot meet the construction requirements of highway and railway tunnel projects;
[0143] In Comparative Example 4, the water-based polyurethane emulsion in the airtightness modifier was removed, there was a lack of connection mechanism between the polyethylene fiber and the carbon fiber, the chain segment was easily broken after the composite fiber was folded into a spiral, there were fewer three-dimensional spiral structures in the concrete system, the filling effect between the components was poor, the concrete system had a high porosity and poor airtightness, and could not meet the construction requirements of highway and railway tunnel projects;
[0144] In Comparative Example 5, the plasma modification step of polyethylene fiber was eliminated, the interface performance of polyethylene fiber was significantly reduced, the fiber surface collection sites were less, and it was impossible to connect with the binding sites on the carbon fiber surface, and it was difficult to bend and fold to form a three-dimensional spiral structure. The filling effect between the components was poor, the concrete system had a high porosity and poor air tightness, and could not meet the construction requirements of highway and railway tunnel projects.
[0145] In Comparative Example 6, the carbon fiber surface modification step was eliminated, and the interface performance of the carbon fiber was significantly reduced. There were fewer assembly sites on the fiber surface, which could not be connected with the binding sites on the polyethylene fiber surface, and it was difficult to bend and fold to form a three-dimensional spiral structure. The filling effect between the components was poor, and the concrete system had a high porosity and poor air tightness, which could not meet the construction requirements of highway and railway tunnel projects.
[0146] The present application provides a high-airtightness concrete, a preparation method thereof and an application thereof, wherein the high-airtightness concrete is composed of silicate cement, coarse aggregate, fine aggregate, an airtightness modifier, a water reducer, an air entraining agent, an internal curing agent and an appropriate amount of water, wherein the airtightness modifier is composed of plasma-modified polyethylene fiber, carbon fiber and water-based polyurethane emulsion, and the polyethylene fiber and the carbon fiber are modified, the connection sites on the surface of the polyethylene fiber and the carbon fiber are enriched, and a three-dimensional spiral network structure is formed in combination with the water-based polyurethane emulsion, and the airtightness modifier is introduced into the concrete system, and the three-dimensional spiral network structure can be filled between the components, and combined with silicate cement and aggregate, the gaps between the components are filled, and the three-dimensional network structure is filled in the gaps between the components, so as to effectively reduce the porosity of the concrete and significantly improve the airtightness of the concrete. When the tunnel passes through a coal seam rock mass containing gas, the leakage of harmful gases such as gas can be effectively prevented, the risk factor in the tunnel project can be reduced, and the personal safety of the construction personnel can be ensured. The concrete has the advantages of simple operation, broad application prospects and easy promotion and implementation.
[0147] The above are only embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high airtightness concrete, characterized in that: The material is composed of the following components by weight: 37-49 parts of silicate cement, 95-113 parts of coarse aggregate, 77-85 parts of fine aggregate, 26-36 parts of air tightness modifier, 2-5 parts of water reducer, 1-3 parts of air entraining agent, 1-3 parts of internal curing agent and appropriate amount of water; Wherein, the air tightness modifier is composed of the following components by weight: 6-7 parts of plasma-modified polyethylene fiber, 5-8 parts of carbon fiber and 15-20 parts of waterborne polyurethane emulsion; The water-cement ratio of the high airtightness concrete is 0.21-0.
27.
2. The high airtightness concrete according to claim 1, characterized in that: The preparation method of the plasma-modified polyethylene fiber comprises the following steps: Step 101. Put the polyethylene fiber and excess acetone into a soaking tank, soak the polyethylene fiber in acetone for 20 minutes to 30 minutes, and after the soaking is completed, wash with deionized water and dry in sequence to obtain primary polyethylene fiber; Step 102. The primary polyethylene fiber prepared in step 101 and excess acid solution A are put into a pickling tank, and the primary polyethylene fiber is immersed in the acid solution for 30s-50s. After the pickling is completed, the fiber is neutralized with alkaline solution, washed with deionized water, and dried to obtain a secondary polyethylene fiber. Step 103. The secondary polyethylene fiber prepared in step 102 is transferred to the reaction chamber of a plasma cleaning machine. After the gas impurities in the reaction chamber are extracted, the reaction is carried out for 4 min to 6 min under the conditions of N2 atmosphere, a reaction chamber pressure of 150Pa-220Pa, an output DC voltage of 720V, and an output power of 30W to obtain plasma-modified polyethylene fiber.
3. The high airtightness concrete according to claim 1, characterized in that: The carbon fiber is subjected to surface modification treatment, and the surface modification treatment comprises the following steps: Step 201. Put the carbon fiber and excess acetone into a soaking tank, soak the carbon fiber in acetone at 120° C. and 2.2 MPa for 11 min to 16 min. After the soaking is completed, wash with deionized water and dry in turn to obtain primary carbon fiber; Step 202. The primary carbon fiber, potassium dichromate powder and acid solution B prepared in step 101 are put into a pickling tank, and the primary carbon fiber is soaked in the acid solution for 11s-17s. After the pickling is completed, the primary carbon fiber is neutralized with alkaline solution, washed with deionized water and dried to obtain secondary carbon fiber; Step 203. Put the secondary carbon fiber and tetrabutyl titanate prepared in step 202 into a reactor, and react for 12 min-18 min in a water bath at 50° C., a reaction pressure of 1.3 MPa, and a stirring frequency of 1200 rpm-1500 rpm to obtain a finished carbon fiber product.
4. A high airtightness concrete according to claim 2 or 3, characterized in that: In step 101, the diameter of the polyethylene fiber is 14 μm-18 μm, the length of the polyethylene fiber is 7 mm-14 mm, and the elastic modulus of the polyethylene fiber is 88 GPa-91 GPa; In step 201 , the diameter of the carbon fiber is 10 μm-15 μm, the length of the carbon fiber is 5 mm-10 mm, and the elastic modulus of the carbon fiber is 220 GPa-250 GPa.
5. A high airtightness concrete according to claim 2 or 3, characterized in that: In step 102, the acid solution A is a sulfuric acid solution with a mass fraction of 43%-57%; In step 202, the acid solution B is prepared by compounding a hydrochloric acid solution with a mass fraction of 31%-36% and a hydrofluoric acid solution with a mass fraction of 41%-55% in a mass ratio of 5:
1.
6. The high airtightness concrete according to claim 1, characterized in that: The preparation method of the airtightness modifier comprises the following steps: putting plasma-modified polyethylene fiber, carbon fiber and aqueous polyurethane emulsion into a reactor in sequence according to a preset ratio, reacting for 20 min-33 min under the conditions of a reaction temperature of 48°C-55°C, a reaction pressure of -0.01 MPa and a stirring frequency of 1100 rpm-1300 rpm, and obtaining the airtightness modifier.
7. The high airtightness concrete according to claim 1, characterized in that: The coarse aggregate is selected from any one of basalt, pebble, limestone, granite, gabbro, gneiss, marble or a mixture of more than one of them.
8. The high airtightness concrete according to claim 1, characterized in that: The fine aggregate is selected from any one of zeolite powder, slag, river sand, waste glass powder, volcanic ash, rice husk ash, lime powder, glutinous rice flour, coal powder, microsilica powder, or a mixture of more than one of them.
9. The high airtightness concrete according to claim 1, characterized in that: The particle size of the coarse aggregate is 40mm-60mm; The particle size of the fine aggregate is 5 μm-12 μm, and the specific surface area of the fine aggregate is 145000 cm 2 / g-188500cm 2 / g.
10. A method for preparing high airtightness concrete, which is used to prepare the high airtightness concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: Ingredients: weigh each component according to the preset target ratio; Initial mixing: according to the preset target ratio, put silicate cement and coarse aggregate into a concrete mixer, stir for 15 minutes at room temperature and a stirring frequency of 1500 rpm to obtain the initial mixture; Second mixing: according to the preset target proportion, put the primary mixture, fine aggregate, air tightness modifier, water reducer, air entraining agent, internal curing agent and appropriate amount of water into the concrete mixer in sequence. After stirring for 20 minutes at a stirring temperature of 60°C, a stirring pressure of -0.05MPa and a stirring frequency of 1200rpm, a high air tightness concrete product is obtained.